The structure of public limited companies : amended proposal for a fifth directive - Commission of the European Communities (Luxembourg : Commission of the European Communities, 1983)
The proposal for a fifth directive on the structure of public limited companies was first presented to the Council in 1972. The Economic and Social Committee has issued two opinions on the proposal after the publication of the green paper. The European Parliament debated the proposal and the green paper exhaustively both in its committees. The purpose of this amended proposal for a directive is essentially to take account of these opinions.
"Amended proposal for a fifth directive founded on article 54 (3) (g) of the EEC treaty concerning the structure of public limited companies and the powers and obligations of their organs presented by the Commission to the Council on 19 August 1983."
ne 28/03/2019
Ref
Keywords: Public limited companies; Europe